Phonological awareness skills and reading in children who are at risk for learning disability: Role in the Indian context? - Shanbal, Jayashree C; S P, Goswami; S, Chaitra; S, Prathima (Journal of All India Institute of Speech and Hearing, 2010)
Phonological awareness in young school going children has always been the emphasis on children learning to read and write English, especially in the western context. Its importance and relevance to children learning English in the Indian context has just begun. Whether phonological awareness skills are equally crucial for literacy skills in young Indian children is still been explored. Yet another challenge is to study these skills in children who are at risk for learning disability. Hence, the present study necessitates to research phonological awareness skills in typically developing children and in children who are at risk for learning disability. The aim was to study phonological awareness skills and reading in typically developing children and children who are at risk for learning disability. Two groups of subjects in the age range of 36 years participated in the present study. The control group consisted of sixty typically developing children (N = 60) and the clinical group consisted of twelve children (N=12) who are at risk for learning disability. All the children studied in schools with English as the medium of instruction. The results of this study indicated that in phonological awareness, the older children (5-6years) fulfilled 60% criteria on phoneme blending, phoneme identification and phoneme substitution tasks. Other skills were still in the process of development. Children who are at risk for LD did not score on any of the sub-skills of phonological awareness. Typically developing children scored better for reading words than reading non words. Children at risk for LD, performed poorer on both reading words and non words when compared to typically developing children. Overall, performance on reading task was better than phonological awareness tasks. This study has implications on early identification and remediation for children at risk for learning disability.